Development and validation of an instrument to measure the persuasion effects on parents after using the persuasive mobile child obesity monitor app - M., Moosa Qasim; M,, Ahmad; Omar, Mazni; Abdul Nasir, Zulkifli; Abu Bakar, Juliana Aida (American Scientific Publishers, 2019)
With the advent of technology, mobile healthcare (m-healthcare) applications have been developed to help people in managing their daily lives. In order to improve the use of m-healthcare applications, persuasive components in m-healthcare are vital for changing behavior. However, there is no single agreement on how to measure the level of persuasion of users especially in m-healthcare for behavior change. Therefore, majority of researchers attempt to measure the level of users’ acceptance or attitude. So, this paper focuses on the development and validation of a generalized instrument to measure the persuasion effects which targets different group of users. Also, this work is aimed to design and evaluate an instrument to measure the persuasion perspectives of parents using the Persuasive Mobile Child Obesity Monitor (PMCOM) app. Based on the literature review analysis, there are three variables that depend on the persuasion theories which include trigger, ability and motivation that lead to behavior change. These variables have five dimensions that include reminder, reduction, historical information, suggestion and praise. All dimensions are used to establish the required behavior when integrated into the mobile application. The results of an evaluation among 58 parents show that the design of a persuasive instrument based on the generalizable process can provide guidance and information in the construction and validation of the questionnaires for any future studies.